Ціннісні орієнтири людини постсучасності - Стасевська, Оксана Анатоліївна (НТУ "ХПІ", 2016)
Стаття присвячена дослідженню людини постсучасного культурного простору, аналізу її здатності стати активним суб'єктом творення та оновлення вищих духовних цінностей. У статті розглядаються філософські інтерпретації осмислення людського існування з точки зору вибору ціннісних орієнтирів в контексті культури постсучасності, аналізується сутність самої людини, що потребує відповіді на питання, якими є характерні ознаки людини постсучасності.

The article investigates human postmodern cultural space, analyzing its ability to become an active subject of creation and renewal of higher spiritual values. The article deals with philosophical interpretations understanding of human existence in terms of choice of values in the context of the culture of modernity, analyzes the essence of the person that needs to answer the question, what are the characteristic features of human modernity. The real situation becoming valuable human meanings of the modern world is quite complicated: the formation of a system acceptable to all values that promote human spiritual renewal continues. Signs of the times are rather values prostration, value-orientation confusion of man that causes passivity life position, social apathy and frustration. In our view, way out of this situation could be the formation of a universal system of spiritual and moral values of life purport. The denial of this possibility and necessity heard both theoretical and practical level, defending pluralist position. However, reality clearly shows that pluralism of value orientations values converted into anarchy. As a result we have a lack of moral principles in all areas of human activity, mass manipulation of public consciousness and personal, spiritual and moral impoverishment of disorientation and even personality. Analysis of human culture in the context of modernity reveals a number of features that effectively demonstrate its dehumanization, depriving her of basic human qualities, becoming a hybrid of man and machine. The dramatic transformation in society that have occurred over the past decade have led to a reassessment of the significance of most fundamental values. Man modernity lost value criteria of life and work, the correctness or incorrectness of different personal values.
Valued reference-points of man of post-contemporaneity enterprise
Keywords: суспільство інформаційне; суспільство технократичне; глобалізація; informative society; technocratic society; globalization